The role of personality traits in mediating the relation between fear of negative evaluation and social interaction anxiety - Macovei, Crenguța Mihaela; Bumbuc, Ștefania; Martinescu-Bădălan, Fabiana (Frontiers in Psychology, 2023)
Social interaction anxiety and fear of negative evaluation have many maladaptive outcomes and it is therefore necessary to identify those psychological or social factors that make people vulnerable to them, in order to counteract their effects. One of these factors is the individual's personality structure: some personality traits increase individuals' vulnerability to symptoms of social anxiety, while others protect them. The aim of this paper is to analyse the role of HEXACO personality traits in mediating the relationship between fear of negative evaluation and social anxiety in a sample of 352 cadets from the Land Forces Academy of Sibiu. The relationships between these constructs were analysed employing the structural equation modeling (SEM) and using several hypothesised models; two of which were ultimately validated. In the first model, the fear of negative evaluation has an indirect effect on social interaction anxiety through the mediation of extraversion, conscientiousness and altruism, separately. Furthermore, extraversion, conscientiousness, and altruism play a serial mediating role in the association between the fear of negative evaluation and social interaction anxiety. In the second model, the fear of negative evaluation has an indirect effect on social interaction anxiety through the mediation of social boldness, liveliness, and organization, separately, but not through altruism. Social boldness, liveliness, and organization played a serial mediating role in the relationship between the two constructs, while altruism moderated the relationship between liveliness, organization, and social interaction anxiety. Analysing the relationship between the individuals' personality traits, social anxiety, and fear of negative evaluation facilitated the identification of ways to foster desirable behaviours in social environments characterized by compliance, discipline, uniformity, and rigor.